1968/2008 - von Treskow, Isabella,von Tschilschke, Christian (Gunter Narr Verlag, 2008)
Eine allgemeingültige Wahrnehmung der Ereignisse von
9783823374633
Keywords: Geschichtsbildung; Mythisierung; Literatur; Fil